A cross-sectional study to determine the prevalence of thyroid autoimmunity in patients with chronic spontaneous urticaria - Pallavi Singh; Vidyadhar R Sardesai (Wolters Kluwer Medknow Publications, 2023)
Background: Chronic spontaneous urticaria (CSU) can be a distressing condition for both the patient and the treating doctor due to the lack of a definite underlying etiology. The condition has been found to be associated with autoimmune (AI) conditions, which brings to light possible pathogenesis being shared by AI conditions and chronic urticaria. This can help us understand the condition better as well as have a bearing on the treatment. Thyroid autoimmunity is one such condition which has commonly been associated with chronic urticaria. Objectives: To determine the prevalence of thyroid autoimmunity in patients with CSU. To determine the correlation between thyroid autoantibodies level and the severity and duration of CSU. Materials and Methods: Forty-eight adult patients of CSU were enrolled, in whom thyroid autoimmunity was determined by detecting the levels of anti-thyroid peroxidase (anti-TPO) antibody. Urticaria Activity Score was used to determine the activity of the disease. Results: Nine out of 48 (18.75%) patients showed raised anti-TPO antibody levels. Eight out of those 9 (88.89%) patients were female. No correlation was found between the duration of disease and the antibody levels. A significant association was found between the disease activity and anti-TPO antibody levels. Conclusion: The prevalence of thyroid autoimmunity is higher in patients of CSU compared to the general population. The condition occurs more frequently and with greater severity in the female population.